A new paradigm of physical development disorder in patients with juvenile idiopathic arthritis - T.V. Marushko; Yu.Ye. Holubovska (Zdorovʹe Rebenka, 2020)
Background. The natural processes of the physical development in a pediatric patient are disturbed by juvenile idiopathic arthritis (JIA). The causes for this are found to originate from the disease pathogenesis, the developmental characteristics of the child’s body, and the chosen JIA therapy. The objective was to evaluate the physical development indices in our JIA patients depending on various treatment regimens in order to synthesize optimal recommendations aimed at preventing growth impairments in this category of patients. Materials and methods. Anthropometry data (growth by Standard Deviation Score), the growth rate for the previous year in 142 patients with JIA, and hand dynamometry in some children were evaluated. The results were compared using both parametric (Student’s t-test) and non-parametric (Mann-Whitney U test) methods, and the correlation was studied by multiple regression analysis. Results. There was no child with oligoarticular form of the disease diagnosed with growth delay during the study. Physical development disorders (height less than –1 SD) were detected in 12 patients (8.5 %) from both groups: in 6 — with the systemic form and in another 6 individuals — with the polyarticular form. When using immunobiological agents (disease-modifying anti-rheumatic drugs), the relative growth velocity was significantly higher in patients with both oligoarticular (U = 225.5, p = 0.009) and polyarticular (U = 222.5, p = 0.0001) forms of the disease. According to the results of multiple regression analysis, the higher was the total disease activity score, the greater was the growth delay. Children with polyarticular (49.0 %) and systemic (54.5 %) forms of JIA had impaired muscle strength. Conclusions. The identification of growth disorders is the basis of an in-depth examination and treatment arrangements in patients with JIA. The degree of disease activity affects growth rates.